Situation Report: Poland, 3 March 1989 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Round-Table Talks Convene / by Anna Swidlicka Initial Round-Table Talks Signal Conflicts to Come / by Louisa Vinton Representation at the Round-Table Talks Participants in the Round-Table Talks Belchatow and the Round-Table Talks / by Roman Stefanowski The Sejm Elections Issue / by Anna Swidlicka Poland's Economic Results in 1988 / by Roman Stefanowski The Polish Labor Party Is Reactivated / by Anna Swidlicka Miscellaneous Items / by Roman Stefanowski